Mutual funds’ strategic voting on environmental and social issues - Michaely, Roni; Ordonez-Calafi, Guillem; Rubio, Silvina (Review of Finance, 2024)
Abstract Environmental and social (ES) funds in non-ES families must balance incorporating the stakeholders’ interests they advertise and maximizing shareholder value favored by their families. We find that these funds support ES proposals that are far from the majority threshold, while opposing them when their vote is more likely to be pivotal. This strategy results in a high average support for ES proposals, seemingly consistent with their fiduciary responsibilities, while opposing contested ES proposals. This greenwashing strategy is driven by ES funds in non-ES families who cater to institutional investors. Indeed, these funds experience lower inflows when providing low average support for ES proposals. This strategic voting is not exhibited in governance proposals, nor by ES funds in ES families or by non-ES funds in non-ES families, reinforcing the notion of strategic voting to accommodate family preferences while appearing to meet the fiduciary responsibilities of the funds.